Knowledge structure of emergy theory in the field of eco‐compensation research: A grounded theory approach - Xu, Xiumei; Tan, Yilan; Feng, Chao (Natural resources forum, 2022)
Although emergy theory has made progress in the field of eco‐compensation research, there is still a lack of review articles, summarizing the existing knowledge structure in this area of study. Accordingly, the objective of this paper is to provide a reference for researchers by characterizing the current status of emergy theory in the field of eco‐compensation and to establish the internal logic structure among existing studies, based upon a qualitative analysis of textual data. Inspired by the grounded theory, twelve concepts within five categories of emergy theory were extracted by open, axial, and selective coding of relevant literature. Concepts were extracted from the texts and categories were determined according to the inherent logical relationships among those concepts. The “knowledge structure model of emergy theory in the field of eco‐compensation” was constructed and the following five principal categories were identified: “emergy indicators system,” the “integration of methods and theories,” “research subjects,” “calculation of compensation standards,” and “research concerns.” Moreover, core and supporting genera were also identified from these five axial codes. Finally, the research focuses and hotspots were explored according to the theoretical frameworks as indicated by the core and supporting genera. The findings of this paper provide a reference for researchers to further promote innovation in the application of emergy theory in the field of eco‐compensation.